If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 5(4x + -3) = 4(6x + 4) + -4 Reorder the terms: 8x + 5(-3 + 4x) = 4(6x + 4) + -4 8x + (-3 * 5 + 4x * 5) = 4(6x + 4) + -4 8x + (-15 + 20x) = 4(6x + 4) + -4 Reorder the terms: -15 + 8x + 20x = 4(6x + 4) + -4 Combine like terms: 8x + 20x = 28x -15 + 28x = 4(6x + 4) + -4 Reorder the terms: -15 + 28x = 4(4 + 6x) + -4 -15 + 28x = (4 * 4 + 6x * 4) + -4 -15 + 28x = (16 + 24x) + -4 Reorder the terms: -15 + 28x = 16 + -4 + 24x Combine like terms: 16 + -4 = 12 -15 + 28x = 12 + 24x Solving -15 + 28x = 12 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. -15 + 28x + -24x = 12 + 24x + -24x Combine like terms: 28x + -24x = 4x -15 + 4x = 12 + 24x + -24x Combine like terms: 24x + -24x = 0 -15 + 4x = 12 + 0 -15 + 4x = 12 Add '15' to each side of the equation. -15 + 15 + 4x = 12 + 15 Combine like terms: -15 + 15 = 0 0 + 4x = 12 + 15 4x = 12 + 15 Combine like terms: 12 + 15 = 27 4x = 27 Divide each side by '4'. x = 6.75 Simplifying x = 6.75
| 3(c+7)=36 | | 7(2e-1)-3=6+3e | | x^2+26x-3552=0 | | 3+6x+7+4x= | | 9*x-9=3(3*x-3) | | 4(2x+5)=6(3x-5) | | 25-2x=x | | 3.5d+5.75=2+4.25d | | (5x-8)(2x-6)= | | -19-1+26-37=-1-3m-8+4m | | 8500=-200t^2+3600t | | 3*x+(-4)=6*x-4 | | 90=-2.5b | | 1.3+1.5=1.4 | | 4(2*x+2)=8*x+9 | | 6m-12n= | | .5x+8=1-.25x-7 | | Y=100x^2-81 | | 2a+-2=15.7 | | 55=0.2(55-10e) | | (10x-4)=12 | | 5z-14=8z+4 | | -n+7=n-9 | | x+x(2)+x+86=180 | | -2(6x-4)=8-12*x | | -6d=-8 | | 6-3x+2x^2-x^3=0 | | -x=7x+2 | | 4*x+19=-9-6x | | x+5=7x+2 | | 25-(-5)-7= | | 3x-22+65=180 |